Effect on superhydrophobic surfaces on electrical porcelain insulator, improved technique at polluted areas for longer life and reliability - Ramalla, Isaac; Gupta, Rajeev K; Bansal, Kamal (International Journal of Engineering and Technology, 2015)
This paper proposes a novel technique to enhance the stability of high-voltage insulators, which are affected due to the presence of dust, contamination, electrical stresses in a high moisture content environment. These result in puncture of insulators and heavy loss due to power outages in the transmission lines. To extend its stability, powdered coating is done on the insulators which have insulation property and super hydrophobicity. In this paper, the authors were inspired by the ‘lotus effect', and a nano size powder was developed by sol – gel method and coating is done on the porcelain insulator surface, which passes-out all the electrical testing standards and maintains its insulation property with super hydrophobic nature. The water droplet contact angle of 158.80 and a sliding angle of 80 indicate the super hydrophobic nature on the surface of insulator. The insulator was kept in a highly polluted environment for six months at different locations where no dust was collected on the insulator when compared with an uncoated insulator.